Activation volume and activation energy of the protochlorophyllide phototransformation and the Shibata shift determined with high pressure fluorescence spectroscopy - Solymosi, Katalin (Acta Biologica Szegediensis, 2002)
The kinetics of protochlorophyllide phototransformation and of the subsequent blue shift were studied in homogenates prepared from etiolated wheat leaves using fluorescence spectroscopy at high pressures. The pressure dependence of the processes was studied between 0.1 and 400 MPa. The activation volumes were calculated from the pressure dependence of the kinetical curves of the processes and were compared at 20°C and at 40°C. The temperature dependence of the processes was analyzed at atmospheric pressure (0.1 MPa) between 10°C and 40°C. Th eactivation energy of the processe sat atmospheric pressure was calculated using Arrhenius plot. The simultaneous variation/change of temperature and pressure provides information about the molecular events occuring during the activation of the processes.